Doświadczalna Analiza Nośności Granicznej Rozciąganych Płaskich Prętów z Karbem - Szczepiński, W.; Miastkowski, J. (Engineering Transactions, 1965)
The paper presents the results of experimental investigation of the limit load of flat bars subjected to tension and having symmetric notches at opposite edges. The first set, comprizing 48 mild steeltest-pieces were used chiefly for the investigation of the influence of the width 2b of the test piece (Fig. 1) on the magnitude of the rupture force and the force for which large plastic strain begins to occur, From the experimental curves of Fig. 6 it follows that for bJh > 2 the increase of the force is very small; we can therefore assume that for blh > 2 the test pieces are in a state approaching the plane state of strain. However, considerable dispersion of the values of the coefficient of limit load increase, as obtained from Hill's solution for a perfectly plastic body, has been found. This can be explained in part by a too small width 2c of the grip of the test pieces, A separate set of aluminium alloy test-pieces was used to investigate the influence of the width 2c on the limit load. These test pieces differed only by the dimension 2c and had the ratio bJk = 2. The measurement results are represented in Fig. 14. The upper curve represents the conventional rupture stress, the lower - the yield limit. The vertical dotted line represents the theoretical value c/h = 2.62 obtained by prolonging the net of slip lines (Fig. 15).